Interpretative Models of Newtonian Corpus: historiographic Traditions of Twentieth Century - Orozco-Echeverri, Sergio H. (Estudios de Filosofía, 2007)
This article tries to establish the scopes and limits of the main interpretations on Newton during the 20th century, highlighting on the one hand the textual evidence at disposal, and on the other hand the philosophical and epistemological currents that defines the main features of those interpretations. It will be shown that the rejection of positivism is not sufficient condition for establishing an adequate interpretation and, together with the strengthening of the research from Newton’s manuscript, it is necessary a wider, and more detailed model that those established by some of the most outstanding scholars like Alexandre Koyré, I. Bernard Cohen, Betty Dobbs, and Richard Westfall.